Et bundt våben fra Vimose - Ilkjær, Jørgen (Kuml, 1975)
A bundle of weapons from Vimose An integral find from the weapon offering in Vimose is the main subject of this article. The excavator, Conrad Engelhardt, himself drew attention to this find, but it has not been dealt with since the Vimose publication. The find consists of 29 lance heads (without barbs), 8 spearheads (with barbs) and a silver plated bronze plate from a sword hilt, all wrapped in a piece of woven woollen cloth. No exact parallels to the bronze plate are known, and this article therefore deals exclusively with the 37 spear- and lance heads which have been identified. But spear- and lance heads from the Roman period have never been treated so comprehensively that they can be directly placed culturally and chronologically. The material from the weapon graves, which has furnished type artefacts, comprises in particular sword fittings and shield bosses, in conjunction, of course, with any imports and in very rare cases with brooches. The procedure followed here is therefore a detailed analysis of the spear- and lance heads found in the bundle, an evaluation of the different types, and a comparison with weapons recovered from graves. A prerequisite for a detailed analysis of spear- and lance heads is a definition of elements, appendix 1. In fig. 2 and 3 the various forms of blade/point and socket sections found in spear- and lance heads from Vimose, Nydam, Kragehul, Illerup Ådal and several small votive finds are shown. Lance heads The blade section serves as the basis for the division of the 29 lance heads in the bundle. This element has the advantage that it is often possible to determine even in corroded and fragmented specimens found in graves. The following blade sections are represented: 2 and 2b, 3, 5 and 6. All the lance heads in the bundle have curved blade, except perhaps for no. 24742, which may have had a simple blade. The socket outline varies more, but the concave form predominates with 24 specimens. Only 4 are straight and 1 convex. The lance heads of section 2 and 2b (fig. 4) do not comprise a homogeneous group, since the rhombic blade section is found with both straight and symmetrical concave sides. The socket sections also vary. The total length of the lance heads varies between 14.2 and 23.3 cm and the average blade thickness is only 0.65 cm as against 1.15 cm in lance heads of blade section 6. None of the lance heads is decorated. It is characteristic of the lance heads with blade section of form 3 (fig. 5 and 6) that the section of the distal 8 cm changes to form 2. The overall length of the two specimens is about 21 cm and one is decorated with chasing on both socket and blade. Lance heads with this blade section are not known from Scandinavian grave finds and will not be treated further here. Lance heads with blade section of form 5 (fig. 7 and 8) merge into form 2 10.0, 7.0 and 10.5 cm from the point respectively. The socket sections are respectively of form 6, 2 and 5. Two of the three socket sections are characterized by small facets of uniform width. The overall length varies from 20.7 to 33.6 cm, and two of the three heads are chased on the upper part of the socket and on the blade. In spite of the differences in size there are so many common features that the heads are referred to the same type, named after the lance head in the Lynghøjgård grave and defined:- 1: blade section of form 5, merging into form 2 more than 3 cm from the point and 2: curved blade. The lance heads with blade section of form 6 (fig. 13-22) are divided into various types, called after some of the types shown in the scheme fig. 29. The Gamme type (fig. 13 c) is defined primarily on the shape of the socket, which is cylindrical, i. e. with a straight profile and the greatest thickness minus the smallest thickness less than 0.5 cm. The blade can vary, Lance heads with blade section 2 and 26 and 6 also being referred to the type. The blade may be simple or curved. The Vennolum type (fig. 14) is defined by:- 1: blade section of form 6, 2: curved blade, 3: concave, not cylindrical socket, socket length less than 3/8 of the blade length, 5: blade width greater than 3.5 cm. The Skiaker type (fig. 16) has the same blade section, blade shape and socket section as the Vennolum type, but the socket length is more than or equal to 3/8 of the blade length and the blade width less than or equal to 3.5 cm. These lance heads are shown in the table fig. 12, where also the Svennum type (20), which does not occur in the bundle, is included. The Gamme type is in the bundle represented by 1 specimen, the Vennolum type by 7, and the Skiaker type by 8. In addition there are 2 hybrid forms (Vennolum/Skiaker) and 2 special forms. A more detailed description of lance heads of the Vennolum and Skiaker types is found in fig. 10 and 11, where the dimensions are shown in histogram form. 6 of the 7 lance heads of Vennolum type are chased on the blade and one of them has in addition metal inlay. All lance heads of Skiaker type in the bundle are chased. Chasing and inlays are seen in fig. 17-22. Spearheads There are only 8 spearheads in the bundle. All the spearhead types from Vimose are therefore used in the type classification, except specimens with a boss on the socket, those with only one barb, those with another socket section than forms 5 and 6 and those with convex socket. Every spearhead in the bundle has a curved blade and 7 out of 8 have a concave socket outline, the remaining specimen having a convex one. The point section is in all specimens of form 2 and only socket form 5 or 6 is represented, i. e. with 10 or 12 facets of uniform width. The Simris spearhead type (fig. 26) (see Simris grave 41 in the scheme fig. 29) is defined by:- 1: curved blade, 2: point/socket ratio greater than or equal to 0.66. The Skiaker spearhead type (fig. 27 and the Skiaker grave in the scheme fig. 29) is defined by:- 1: curved blade, 2: point/socket ratio greater than or equal to 0.33 but less than 0.66 and 3: point width less than 1.2 cm. The scheme fig. 23 also shows the Svennum spearhead type which does not occur in the cloth bundle (21). This differs from the Skiaker type in that the point width is larger than or equal to 1.2 cm. The Simris type is represented by 4 specimens, the Skiaker type by 3, and in addition there is a single spearhead of special form (fig. 25). None of the spearheads is chased, but one is furnished with metal inlay (fig. 26 a and fig. 28). Chronology Although all spear- and lance heads in the bundle were obviously deposited at the same time, one would still expect to be able to indicate time differences, because spear- and lance heads are unlikely to be of the same age at the time of deposition. A number of finds from weapon-containing graves in Denmark, Norway and Sweden, containing lance heads of types represented in the bundle, serve as a foundation for a relative chronology. These graves are shown in the scheme fig. 29. Lance heads with blade section 2 and 2b are known from inter alia the Danish graves Harnebjerg and Kagstedhøj and a Swedish grave from Kornettskogen. They were found with shield bosses with conical top or with pointed bosses, dated to the early Roman Iron Age. The Kornettskogen grave also contained a single-edged sword. The lance head of blade section 3 is not as far as I know found in Scandnavian graves. The Lynghøjgård type of lance head was found in the Lynghøjgård grave with a spearhead with a boss on the socket and only one barb, a single-edged sword, and a shield-handle fitting with nails with thimble-like heads. The Norwegian grave of Østre Hovin contains a variant of the Lynghøjgård type, a spearhead with point section 2b, a single-edged sword, a rod shield-boss and a shield-handle fitting with offset ends. According to these finds the Lynghøjgård lance head type should be referred to the early Roman lron Age. In 6 of 9 graves with lance heads of Gamme type, spearheads with a boss on the socket were also found, and in 6 out of 8 graves with shield bosses there are rod bosses, whilst in the other two there are pointed bosses. Further, 4 out of 6 swords are double-edged short swords. In graves with lance heads of Vennolum type there are also characteristic common features. All the shield bosses are of the semicircular type, 4 of which have an added top. All the swords, apart from the double-edged short sword in the Vennolum grave, are double-edged long swords. The spearhead types are, however, different. The Norwegian grave from Hunn contains one spearhead with bossed socket; 3 spearheads are of Simris type, and 2 of Skiaker type. The Øvre Skiaker grave is the only certain case of a combination of the Skiaker types, but this probably also applies to Simris grave 88. The seriated type combination diagram fig. 30 comprises all the graves from the scheme fig. 29 and it is shown that the graves in the upper part of the diagram should be referred to the early Roman lron Age. Simris grave 88 at the bottom of the diagram contains a fibula with a tall pin catch (Almgren VII, 196), which is late Roman Iron Age. The Norwegian grave from Gullen contains, besides the weapons, two strongly profiled fibulae (Almgren IV, 88) and a bronze vessel of Eggers’ type 44. The fibulae normally belong to the early Roman Iron Age but are of a developed form, and the bronze vessel is known in this form from both the early and the late Roman period. The Gullen grave is thus most probably attributable to the beginning of the late Roman Iron Age. The graves with lance heads of Gamme type must be placed between the early Roman Lynghøjgård grave and the Gullen grave, but a boundary between the early and the late Roman period within this group of graves cannot be demonstrated, for they lack fibulae and the imported ware does not afford critical dating. There are thus only weapons remaining as a basis for dating. The spearhead with bossed socket was found in the Hunn grave and the rod boss disappears in the present material, before the advent of the shield boss with semicircular top. The single-edged sword in some of the graves of the group points back to the early Roman Iron Age, whereas the double-edged short sword in others points forward to the later Roman period, since the Vennolum grave contains one. The Vennolum grave is otherwise characterized by the double-edged long sword. All these features suggest that a number of the graves with lance heads of Gamme type should be referred to the early Roman Iron Age, whilst others may be referred to the late Roman Iron Age, to which also the Vennolum and Skiaker groups must be dated. The youngest artefacts in the bundle are thus from the late Roman Iron Age and most probably the beginning, because the Svennum types, which mainly belong to Eggers’ period C2, do not occur in Vimose, either in the bundle or in the find as a whole. Battle damage or deliberate destruction As is apparent from the illustrations of the individual spear- and lance heads in the cloth bundle, many of the pieces are bent and hacked. In a few there are stubs of spear shafts, but in the majority the shafts have completely disappeared. With respect to the damage, Engelhardt writes (22) that even if, for example, hacks can easily derive from battle, the deliberate destruction after the battle is obvious, nearly everything having been deposited in an unusable state for the owner. This conception of an extensive and deliberate destruction is also emphasized by Brøndsted (23). Neither Brøndsted nor Engelhardt rules out battle damage, but the picture of an almost total destruction in the sacrificial phase is the one which stands out in the mind of the reader. All the shafts of lances and spears in the bundle are broken and only a few stumps are left, but with respect to the points the destruction is far from total. Only exceptionally can an unequivocal deliberate spoiling of the points be recognized. 7 points without hacks or bends could have been used again after rehafting and many of the bent pieces would be usable after very little repair. Interpretation of the weapon offerings Brøndsted conceived the entire Vimose find as the result of two or more depositions, one in the late Roman Iron Age and at least one in the early Roman Iron Age, while Ørsnes underlines the possibility that the main part of the Vimose find can be the result of one deposition, based on the conclusions drawn from the Ejsbøl Nord site, which covered a great span of time. However, Scandinavian grave finds do not suggest that antiquated weapons were used to any extent. In the cloth bundle there were indeed 11 lance and spearheads, which are known in corresponding form from the early Roman Iron Age, but this can be explained by the time of deposition being close to the transition between the early and the late phase. Types of swords, shield bosses and spear- and lance heads which are not known from weapon graves of the Scandinavian late Roman Iron Age suggest that the Vimose find should be divided into several depositions from the early Roman Iron Age, comprising about 1/3 of all lance points and 1/5 of all spearheads, and one deposition in the late Roman Iron Age with the remaining 2/3 of the lance heads and 4/5 of the spearheads. In the weapon graves from the late Roman Iron Age a spearhead nearly always accompanies a lance head in the Scandinavian area. Only occasionally do two lance heads occur together (3), and certain examples of, for instance, 2 lance heads and 1 spearhead or other combinations with more than 2 spear- or lance heads are not known. In the early Roman Iron Age there are far more lance heads than spearheads. One would therefore expect to find most lance heads in the weapon offerings of the early Roman Iron Age, while depositions from the late Roman Iron Age should comprise equal numbers of spear- and lance heads. These circumstances fit Vimose’s early Roman Iron Age part and the Ejsbøl Nord site from the late Roman Iron Age, but neither the cloth bundle nor the whole late Roman Iron Age part of Vimose fits the picture. Further light may perhaps be cast on the different relations between the number of spear- and lance heads in depositions from the late Roman Iron Age by examining the interpretation models for weapon offerings. If the late Roman Iron Age deposition in Vimose is conceived as a partial sacrifice, then the spoils have been divided into two heaps before the offering, one to be offered and one to be distributed as battle spoils. What is more natural than to imagine battledamaged weapons laid in the heap of weapons destined for sacrifice? In this way it is to a certain extent fortuitous what is offered and one obtains a possible explanation of the disparity between the number of spear- and lance heads in the later part of Vimose and an explanation of why so many weapons are obviously secondarily spoiled, and why so many show battle damage. Ørsnes shows at the Ejsbøl Nord site that various artefact types are represented by almost equal numbers of objects and one must here accept the idea of a total sacrifice. But there is reason to show caution about applying the same model to different depositions. Skedemosse, which consists of many small depositions, cannot be compared with the different Danish weapon offerings, with the possible exception of the Thorsbjerg find, but not even the Danish depositions can apparently be interpreted uniformly. Some possibly represent partial sacrifice, others total. Jørgen Ilkjær